Transient ischaemic attacks: mimics and chameleons. Issue 1 (22nd January 2014) - Nadarajan, V; Perry, R J; Johnson, J; Werring, D J
Abstract : Suspected transient ischaemic attack (TIA) is a common diagnostic challenge for physicians in neurology, stroke, general medicine and primary care. It is essential to identify TIAs promptly because of the very high early risk of ischaemic stroke, requiring urgent investigation and preventive treatment. On the other hand, it is also important to identify TIA 'mimics', to avoid unnecessary and expensive investigations, incorrect diagnostic labelling and inappropriate long-term prevention treatment. Although the pathophysiology of ischaemic stroke and TIA is identical, and both require rapid and accurate diagnosis, the differential diagnosis differs for TIA owing to the transience of symptoms. For TIA the diagnostic challenge is greater, and the 'mimic' rate higher (and more varied), because there is no definitive diagnostic test. TIA heralds a high risk of early ischaemic stroke, and in many cases the stroke can be prevented if the cause is identified, hence the widespread dissemination of guidelines including rapid assessment and risk tools like the ABCD2 score. However, these guidelines do not emphasise the substantial challenges in making the correct diagnosis in patients with transient neurological symptoms. In this article we will mainly consider the common TIA mimics, but also briefly mention the rather less common situations where TIAs can look like something else ('chameleons').